2017
DOI: 10.1111/mms.12467
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and sex on the vocal repertoire of the Antillean manatee (Trichechus manatus manatus) and their responses to call playback

Abstract: Limited information is available regarding the acoustic communication of Antillean manatees, however, studies have shown that other manatee taxa produce vocalizations as a method of individual recognition and communication. Here, the acoustic signals of 15 Antillean manatees in captivity were recorded, aiming to (1) describe their acoustic repertoire, (2) investigate the influence of sex and age on vocalization, and (3) examine manatee responses to call playback. Six acoustic signals ranging in mean fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
(74 reference statements)
0
16
0
2
Order By: Relevance
“…Vocal repertoires are limited for rhinos and calls were observed in fewer social contexts such as mating, aggression, and during play (Policht et al, 2008). In addition to information related to age (Sousa‐Lima et al, 2002, 2008; Umeed et al, 2017), sex (Sousa‐Lima et al, 2008; Steel, 1982; Umeed et al, 2017), and individuality (Sousa‐Lima et al, 2008), manatee vocalizations contain motivational information in their calls. Results in this study are also similar to what has been reported for phylogenetically related species such as the African elephant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocal repertoires are limited for rhinos and calls were observed in fewer social contexts such as mating, aggression, and during play (Policht et al, 2008). In addition to information related to age (Sousa‐Lima et al, 2002, 2008; Umeed et al, 2017), sex (Sousa‐Lima et al, 2008; Steel, 1982; Umeed et al, 2017), and individuality (Sousa‐Lima et al, 2008), manatee vocalizations contain motivational information in their calls. Results in this study are also similar to what has been reported for phylogenetically related species such as the African elephant.…”
Section: Discussionmentioning
confidence: 99%
“…Manatee vocalizations exhibit frequency modulations that can occur in the beginning, middle or end of the call (Nowacek et a l., 2003; O'Shea & Poché, 2006). Differences in structure in manatee vocalizations have been attributed to age (Sousa‐Lima et al, 2002, 2008; Umeed et al, 2017), sex (Sousa‐Lima et al, 2008; Steel, 1982; Umeed et al, 2017), and individuality (Sousa‐Lima et al, 2008). However, it has also been hypothesized that frequency modulations observed in manatee calls could be related to motivational state (O'Shea & Poché, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The vocal repertoire of Sirenians varies between three and six call types depending on the mode of classification (Anderson & Barclay, 1995;Brady et al, 2020;Steel, 1982;Umeed et al, 2018). However, for most species, we lack sufficient data to adequately characterize the breadth and function of their vocal repertoire.…”
Section: Structure and Function Of Vocalizationsmentioning
confidence: 99%
“…Los resultados que encontramos para los órdenes Carnívora, Sirenia, Artiodactyla y Rodentia fueron muy escasos; esto evidencia un fuerte vacío en el conocimiento en órdenes con un gran potencial de trabajo (Lozano-Flórez et al, 2021). El comportamiento acústico puede proporcionar señales filogenéticas (Peters & Tonking-Leyhausen, 1999;Cap et al, 2008), estimar abundancias (Thompson et al, 2010), apoyar herramientas de reconocimiento individual Della Libera et al, 2015;Carlson et al, 2020), y por ende, brindar información sobre las poblaciones (Umeed et al, 2018) en especies difíciles de capturar o en categoría de peligro (p. ej., manatíes) en las que las herramientas acústicas tienen una ventaja más, al ser métodos no invasivos.…”
Section: Biota Colombiana 22 (1) -2021 |unclassified